Eugenische Vernunft Eingriffe in die reproduktive Kultur durch die Medizin 1900-2000 - Wolf, Maria A. (2008)
This is a study about the causes and consequences of the eurgenic intrusions into our society´s reproductive culture by medicine over the course of the twentieth century. By the turn of the twenty-first century, such scientific intrusions through biotechnological selection at the very beginning of a human´s life have become socially acceptable and part of the task of family planning. Of intrinsic interest is the goal of subjecting the normative ideal images of family, motherhood, fatherhood and childhood - which through medical science have advanced eugenic intrusions into the social organization of the species "reproduction" - to a gender-sensitive analysis. This study also highlights how these ideal images are integrated into the development of the biotechnologies of conception and selection, and how these technologies in turn influence familiy planning. The issue are analyzed against the background of social and scientific developments which accompanied and made possible the rise of eugenic rationality in the twentieth century. The sources used for this analysis are medial studies published in the journal Wiener Klinische Wochenschrift between 1900 and 2000; the methodology applied is discourse analysis. The project was financed by a research grant (APART) under the auspices of the Austrian Academy of Science (ÖAW). This research demonstrates: which concepts of gender and generation within the families are inherent to the eugenic ideal images; which social transformation processes were integrated into these ideal images; how and why parenthood and childhood were scientiffically rationalized and modernized; the demands which have increasingly confronted parents over the past decades as regards successful instruction and education; the duties which emanated in the namen of the child´s well-being; and the reasons for which biotechnological selection at the very beginning of human life currently has a sweeping influence on motherhood and childhood. Finally, the study demonstrates that the existing reproductive culture in our society is infused by eugenic rationality. A further investigative dimension of the eugenic mainstream is also developed by virtue of the approach in which the focus consistently points to the scientific reorganization of the entire context of reproduction. And by virture of which the scientification of the reproductive culture is examined and analyzed by contextualizing Austria´s twentieth-century social and socio-political history. In addition, a profound and exemplary critiqu of science is elaborated by employing the approaches of the sociology of science as well as the history of science and drawing upon the Austrian example of (bio)medicine and bio(medical) technologies of conception and selection. Science is presented in its cultural and political entanglement as a bastion of hegemonic masculinity, staking a claim to the connection between science and responsibility.